Programmed death ligand 1 (PD-L1) status and tumor-infiltrating lymphocytes in hot spots of primary and liver metastases in prostate cancer with neuroendocrine differentiation - Hardenberg, Jost von; Hartmann, Sarah; Nitschke, Katja; Worst, Thomas; Nuhn, Philipp; Weis, Cleo-Aron Thias; Erben, Philipp (Clinical genitourinary cancer, 2019)
Background - Prostate cancer with neuroendocrine differentiation (NEPCA) shares similarities in tumor biology with small-cell lung cancer. While immunotherapies were successfully tested in small-cell lung cancer, and programmed death ligand 1 (PD-L1) expression arises as an essential predictive biomarker, the local immune status in NEPCA is still poorly described. - Patients and Methods - Paraffin-embedded tissue samples of 39 patients (7 adenocarcinomas with neuroendocrine differentiation [ACA NED], 20 small-cell neuroendocrine carcinomas, 2 well-differentiated neuroendocrine tumors of NEPCA, and 10 adenocarcinoma liver metastases) were examined retrospectively by immunohistochemistry of chromogranin A (CGA), CD56, synaptophysin (SYN), CD3, and PD-L1. Laser capture microdissection was used for neuroendocrine hot-spot evaluation for additional real-time reverse transcription-quantitative PCR analysis (PD-L1, CGA, CD56, SYN, GRP, ASCL1, and DLK1). - Results - PD-L1 immunohistochemistry expression in NEPCA was observed by assay E1L3N in 5 (20.8%) of 24 samples, but not by assay 22c3. Gene expression of PD-L1 could be evaluated in 18 (62%) of 29 samples. Nine (69%) of 13 prostate specimens and 2 (40%) of 5 liver metastases were positive for PD-L1. In ACA NED 4 (80%) of 5 and in small-cell neuroendocrine carcinomas 6 (50%) of 12 specimens were positive for PD-L1. Tumor-infiltrating lymphocytes ≥ 10% were observed in 9 (37.5%) of 24 specimens. Low ASCL1 expression was observed in liver metastases. - Conclusion - These data identify molecular PD-L1 features in NEPCA. The predictive role of PD-L1 status and tumor-infiltrating lymphocytes in NEPCA remains to be established.
Available online 21 December 2018
Gesehen am 22.05.2019